Respuesta :
Answer: m = kn/p3 = k*2/1 --> k = 3/2m = 3n / 2p
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
Given m varies inversely as n then the equation relating them is
m = [tex]\frac{k}{n}[/tex] ← k is the constant of variation
To find k use the condition m = 3 when n = 2
3 = [tex]\frac{k}{2}[/tex] ( multiply both sides by 2 to clear the fraction )
6 = k
m = [tex]\frac{6}{n}[/tex] ← equation of variation
when n = 12 , then
m = [tex]\frac{6}{12}[/tex] = [tex]\frac{1}{2}[/tex] → B